Physical and Psychosocial Correlates of Occupational Physical Injury in the Global Construction Industry: A Scoping Review - Aaron S Howe; Jeremy Tan; Beatrice Yuen; Harseerat Saini; Natalia Saade-Cleves; Donia Obeidat; Maryam Shahzad; Vijay Kumar Chattu; Ali-Bani Fatemi; Behdin Nowrouzi-Kia (SAGE Publishing, 2024)
Purpose: The construction industry is a diverse sector with exposure to multiple psychosocial and environmental workplace hazards that increase the risk of injury. This scoping review aims to consolidate the existing literature on the physical and psychosocial determinants influencing the risk of occupational physical injuries among construction workers globally. Methods: A scoping review was conducted using the PRISMA extension checklist guided. Literature searches were performed between June and October 2023 in electronic academic databases. Results: A total of 77 studies were identified, encompassing various geographical regions, including North America (n = 29), Africa (n = 18), Europe (n = 12), Asia (n = 9), the Middle East (n = 5), and Oceania (n = 4). The review identified physical and psychosocial factors in 3 domains influencing occupational physical injuries: workplace physical environment (eg, exposure to physical hazards, availability and utilization of personal protective equipment, company size, and job type), workplace culture (eg, psychosocial stressors, gender-related barriers, migrant and ethnic disparities, educational background), and physical wellbeing, health and aging (eg, age, obesity, sleep quality, marital stats, and physical health status). Notably, workers from social minority groups (eg, women, ethnic and migrant workers) of young (<25 years old) or older ages (45-55 years old) employed in smaller construction companies are vulnerable to increased injury risk and exposure to physical and psychosocial hazards in the workplace. Conclusion: The review emphasizes a global paucity of research examining the implications of physical and psychosocial factors on injury risk within the construction industry. Future research should prioritize investigating the impact of psychosocial hazards on younger and older workers to detect age-related differences in injury rate, treatment access, and work-related health outcomes.